(untitled) (Research, Society and Development, 2021)
Within the framework of ecological models and social empowerment, this study analyzes relationships between contexts and levels of anxiety, depression, socio-political control and future prospects for young institutionalized offenders (N = 175), in three centers in the Federal District of Brasília. In a subsample (n = 52), the relationship between data from young people and professionals from these institutions is also analyzed. In the total sample, the analysis of variance (ANOVA) with a center factor (context) on three levels, young people obtain higher average results in socio-political control and lower in anxiety, in one of the centers. Through contingency tables, we observed that in the same center, the motivations of the professionals are more intense and there is a decrease in fears of insecurity. In addition, we observed correlations between the results of the motivation of professionals´, and the well-being and the socio-political control of young people result´s. In conclusion, the systematic trend of the data emphasizes that the levels of socio-political involvement and well-being follow the intensity of the professionals’ intrinsic motivation. These data provide reflective elements for the intervention that should include professionals and adolescents, as advocated by ecological and social empowerment theories.